Abnormal Accelerating Stress Release Behavior on the Luhuo Segment of the Xianshuihe Fault, Southeastern Margin of the Tibetan Plateau, During the Past 3000 Years - Liang, Mingjian; Chen, Lichun; Ran, Yongkang; Li, Yanbao; Gao, Shuaipo; Han, Mingming; Lu, Lili (Frontiers in Earth Science, 2020)
According to historical earthquake records, the Luhuo segment of the Xianshuihe fault has produced two large earthquakes: the 1816 M7.5 earthquake and the 1973 M7.6 earthquake. The surface ruptures caused by these events remain well preserved. This study focused on the rupture behavior of the Luhuo segment. Based on field investigations, trench excavations and analysis of historical earthquakes, we identified six seismic events that occurred within the past 3000 years, which are dated at 769 BC, 318–545AD, 677–833AD, 1008–1444 AD, 1816 AD and 1973 AD. The recurrence intervals of these events, from oldest to youngest, are approximately 1200, 324, 471, 590 and 157 years. Thus, the recurrence behavior of the fault segment appears inconsistent with time- or slip-predictable models, whereas, the revealed seismic sequence appears consistent with clustering and abnormal accelerating stress release behavior. The fault strike-slip rate during the period of anomalous stress release is approximately 2-3 times faster than the average rate of 8.4 mm/a. Moreover, the Luhuo segment has experienced ongoing high levels of seismic activity over the past 3000 years, and the entire Xianshuihe fault currently shows a high degree of seismic activity. Therefore, we suggest there was a long period of earthquake quiescence prior to 3000 years ago, which might have balanced the high activity and accelerating stress release of current earthquakes.